Expression of epithelial-mesenchymal transition markers at the invasive front of oral squamous cell carcinoma (Journal of Applied Oral Science, 2015)
Oral squamous cell carcinoma (OSCC) is one of the most common malignances. In epithelial-mesenchymal transition (EMT), epithelial cells switch to mesenchymal-like cells exhibiting high mobility. This migratory phenotype is significant during tumor invasion and metastasis. Objective : The aim of this study is to evaluate the expression of the EMT markers E-cadherin, N-cadherin and vimentin in OSCC. Material and Methods : Immunohistochemical detection of E-cadherin, N-cadherin and vimentin was performed on 20 OSCC samples. Differences in the expression of each protein at the invasive front (IF) and in the central/superficial areas (CSA) of the tumor were assessed. Differences in the expression of each protein at the IF of both histologically high- and low-invasive OSCCs were evaluated. Associations among expression of proteins at the IF were assessed. Correlations between the expression levels of each protein at the IF and the tumor stage and clinical nodal status were also evaluated. Results : Reduced expression of E-cadherin was detected in 15 samples (75%). E-cadherin expression was reduced at the IF when compared to the CSA and in high-invasive tumors when compared to low-invasive tumors. All samples were negative for N-cadherin, even though one sample showed an inconspicuous expression. Positive expression of vimentin was observed in 6 samples (30%). Nevertheless, there was no difference in vimentin expression between the IF and the CSA regions or between the low- and high-invasive tumors. Furthermore, no association was observed among protein expression levels at the IF. Finally, no correlations were observed between each protein’s expression levels and tumor stage or clinical nodal status. Conclusions : Reduced E-cadherin expression at the IF and its association with histological invasiveness suggest that this protein is a noteworthy EMT marker in OSCC. Although vimentin was also detected as an EMT marker, its expression was neither limited to the IF nor was it related to histological invasiveness.